PRESTASI BELAJAR MATA PELAJARAN EKONOMI KELAS UNGGULAN DITINJAU DARI ASPEK PEMILIHAN, MOTIVASI BELAJAR DAN SARANA PENUNJANG PEMBELAJARAN - HS, Sudarto; Setiawati, Yuliani (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aim of the research is to describe the influence of choosing outstanding /nonoutstanding class variables, learning supporting equipment, study motivation,towards students achievement of economics lesson. Both partially or integrally.The kinds of research is descritive quantitative. Population used around 200 students, classVIII, SMP Negeri 3 Colomadu. Sample taking is 127 students, consits of 40 outstandingstudents and 87 non outstanding students by using proporsional stratified random sampling.Data collection by using questionaire and documentation, while data analysis used threeways anava techniques. The researcg result show that partially outstanding and nonoutstanding class choosing, students study motivation, learning supporting equipment usagehad influenced students study achievement, but altogether these variables did not influencethat students study achievement.